Evaluation of infrared thermography, arterial Doppler ultrasound, and Doppler echocardiography in healthy adult dogs exposed to a single session of Whole-body vibration at different frequencies - Agostinho, Manuela [UNESP]; Rahal, Sheila [UNESP]; Bonatelli, Shayra [UNESP]; Rosa, Gustavo [UNESP]; Tsunemi, Miriam [UNESP]; Zadra, Vivian; Mamprim, Maria [UNESP]; Takahira, Regina [UNESP]; Souza, Paulo [UNESP]; Santos, Ivan [UNESP] (Veterinary Journal of Ankara University, 2024)
This study aimed to evaluate the infrared thermography, arterial Doppler ultrasound, and Doppler echocardiography in healthy adult dogs exposed to a single Whole-body vibration (WBV) at different frequencies. Sixteen (16) healthy crossbreed dogs males of ages 1 to 5 years, weighing 16.3 to 24.5 kg were enrolled in the study. The dogs were exposed to a single WBV session at frequencies of 30 Hz (5 min), 40 Hz (5 min), and 50 Hz (5 min) with intervals between each frequency exposure of 10 min. The cutaneous temperature, arterial Doppler ultrasound, and Doppler echocardiography were evaluated 10 min before the WBV session, between each frequency, and 1 min after the last frequency. The cutaneous temperature of the regions of the superficial gluteal muscle and biceps femoris muscle of both hind limbs was obtained with an infrared camera. Resistive indexes of carotid and femoral arteries were determined using Doppler ultrasound, and Doppler echocardiography was used to assess the end-systolic volume and end-diastolic volume, heart rate, aortic blood flow velocity, and pulmonary artery flow velocity. Clinical parameters, complete blood count, and serum biochemical (alanine aminotransferase, creatinine, and creatine phosphokinase) were evaluated 10 min before and 60 min after the end of the WBV session. Statistically significant differences were not found in any of the variables among the time points. In conclusion, the protocol of increasing vibration frequencies (30, 40, and 50 Hz) at short-period WBV can be considered appropriate since no change occurred in the parameters evaluated.
Keywords: Exercise; Mechanical vibration; Ultrasound; Vibrating platform